Pelayanan Publik dalam Perspektif Administrasi: Prinsip Kategori Barang, dan Jenis Layanan - Sri Yulianty Mozin; Syarifah Arkani; Siti Nurhaliza Labasir (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Public service is a reflection of the relationship between the state and its citizens, measured through the effectiveness, accessibility, and accountability of bureaucracy in fulfilling basic public rights. This article examines public services from an administrative perspective by focusing on the principles of goods categorization (public goods, private goods, club goods, and common goods) and the classification of service types (goods and services). The study adopts a qualitative literature review approach by analyzing scholarly literature and public policy documents. The findings indicate that a precise understanding of public goods classification has strategic implications for policy formulation, resource allocation, and bureaucratic performance evaluation. This study further highlights that public service reform in Indonesia continues to face structural and cultural challenges, particularly in integrating good governance values and new public service principles. The article recommends a conceptual and institutional renewal to ensure that service systems are more adaptive to digital and inclusive societal dynamics.